Membangun Ulang Media Cetak di Era Digital: Analisis Strategi The New York Times - Setyawan, Irwan (Tuturlogi: Journal of Southeast Asian Communication, 2025)
The collapse of the newspaper industry since 2008 has made many publishers seem to have lost their way. The concept of media convergence, which was initially considered the only way to deal with the development of internet and digital technology, has not been able to make media companies rise from the threat of death. Including the fate of newspapers in Indonesia that have not found a "way out" to maintain their existence. The good news only emerged in early 2024, when The New York Times announced that their digital subscribers had reached 10 million subscribers! The success of The New York Times spontaneously raised new hopes among newspaper managers for their future. What the newspaper from Uncle Sam's country did is certainly interesting to study and analyze. Thus, their success story can be a "road map" for other newspaper industries to achieve the same success. Researchers tried to analyze what steps The New York Times had taken by conducting documentary research, with the main material coming from the company's annual report from 2008 to 2024. The results are expected to be an example for newspaper publishers in the country to take concrete steps in adapting and building innovation to face the digital era in the future.